Palbociclib: Randomized Studies and Real-world Evidence as the Basis for Therapeutic Planning in Metastatic Breast Cancer - Ruckhäberle, Eugen; Schmidt, Marcus; Welt, Anja; Harbeck, Nadia; Wöckel, Achim; Gluz, Oleg; Park-Simon, Tjoung-Won; Untch, Michael; Lux, Michael P. (Geburtshilfe und Frauenheilkunde, 2024)
Endocrine-based combination therapy with an inhibitor of the cyclin-dependent kinases 4 and 6 (CDK4/6 inhibitors) is currently the first-line therapy of choice for patients with hormone receptor-positive (HR+) and human epidermal growth factor receptor 2-negative (HER2−), locally advanced or metastatic breast cancer (mBC). The efficacy and safety of the treatment with palbociclib, the first CDK4/6 inhibitor approved for this indication, have been confirmed in large randomized controlled clinical trials (RCTs) with strictly defined patient cohorts. Since then, many relevant questions about CDK4/6 inhibition with palbociclib for mBC have been investigated in RCTs and real-world studies. Based on this evidence, palbociclib is widely used in clinical practice since many years because of its efficacy and good tolerability.The aim of this review is to summarize findings from RCTs and RWE considering clinically relevant aspects such as safety, tolerability, quality of life and efficacy with a focus on specific questions and patient characteristics. A critical discussion and review of the overall evidence for endocrine-based therapy with the CDK4/6 inhibitor palbociclib can contribute to support therapy decisions in daily clinical practice.Die endokrin basierte Kombinationstherapie mit einem Inhibitor der cyclinabhängigen Kinasen 4 und 6 (CDK4/6-Inhibitor) gilt heute als Erstlinientherapie der ersten Wahl für Patientinnen und Patienten mit hormonrezeptorpositivem (HR+) und humaner epidermaler Wachstumsfaktor-Rezeptor 2 (HER2)-negativem lokal fortgeschrittenem bzw. metastasiertem Mammakarzinom (mBC). Wirksamkeit und Sicherheit einer Behandlung mit Palbociclib, dem ersten in dieser Indikation zugelassenen CDK4/6-Inhibitor, wurden in großen randomisierten, kontrollierten klinischen Studien (RCTs) mit streng definierten Patientinnenkollektiven belegt. Seither wurden zahlreiche relevante Fragen zur CDK4/6-Inhibition mit Palbociclib beim mBC in RCTs und Real-World-Evidenz-Erhebungen untersucht. Auf dem Boden dieser Evidenz wird Palbociclib im klinischen Alltag aufgrund der Wirksamkeit und der guten Verträglichkeit seit vielen Jahren breit eingesetzt.Ziel des vorliegenden Reviews ist es, Ergebnisse aus RCTs einerseits und RWE andererseits unter klinisch bedeutsamen Gesichtspunkten wie Sicherheit, Verträglichkeit, Lebensqualität und Wirksamkeit mit dem Blick auf spezifische Fragestellungen und Patientencharakteristika zusammenzufassen. Die kritische Diskussion und Übersicht zur Gesamtevidenz der endokrin basierten Therapie mit dem CDK4/6-Inhibitor Palbociclib soll dazu beitragen, Therapieentscheidungen im klinischen Alltag zu stützen.
Keywords: metastatic breast cancer; CDK4/6 inhibition; palbociclib; real-world evidence